Overexertion of Effort under Working Time Autonomy and Feedback Provision - Thomas Dohmen; Elena Shvartsman (Institute of Labor Economics (IZA), 2023)
Working time autonomy is often accompanied by output-based incentives to counterbalance the loss of monitoring that comes with granting autonomy. However, in such settings, overprovision of effort could arise if workers are uncertain whether their performance suffices to secure the output-based rewards. Performance feedback can reduce or eliminate such uncertainty. We develop an experiment to show that overprovision of costly effort is more likely to occur in work environments with working time autonomy in the absence of feedback. A key feature of our design is that it allows for a clean measurement of effort overprovision by keeping performance per unit of time fixed, which we achieve by calibrating subjects' productivity on a real effort task ex ante. This novel design can serve as a workhorse for various experiments as it allows for exogenous variation of perfor-mance certainty (i.e., by providing feedback), working time autonomy, productivity, effort costs, and the general incentive structure. We find that subjects provide significantly more costly effort beyond a level necessary to meet their performance targets in the presence of uncertainty, i.e., the absence of feedback, which suggests that feedback shields workers from overprovision of costly effort.
Keywords: C91; D90; I10; J81; 330; working time autonomy; performance uncertainty; feedback provision; incentives; effort; subjective stress